2014
DOI: 10.1371/journal.ppat.1004012
|View full text |Cite
|
Sign up to set email alerts
|

DHX36 Enhances RIG-I Signaling by Facilitating PKR-Mediated Antiviral Stress Granule Formation

Abstract: RIG-I is a DExD/H-box RNA helicase and functions as a critical cytoplasmic sensor for RNA viruses to initiate antiviral interferon (IFN) responses. Here we demonstrate that another DExD/H-box RNA helicase DHX36 is a key molecule for RIG-I signaling by regulating double-stranded RNA (dsRNA)-dependent protein kinase (PKR) activation, which has been shown to be essential for the formation of antiviral stress granule (avSG). We found that DHX36 and PKR form a complex in a dsRNA-dependent manner. By forming this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(166 citation statements)
references
References 43 publications
11
151
2
2
Order By: Relevance
“…In the case of TRIM25, we show that TRIM25 granules are formed upon SeV stimulation and that they colocalized with the SG markers TIAR and GB3P. This finding, also demonstrated by Yoo et al (40) in NDV-infected cells, supports a role for SGs in the antiviral innate immune response (40,41,47).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the case of TRIM25, we show that TRIM25 granules are formed upon SeV stimulation and that they colocalized with the SG markers TIAR and GB3P. This finding, also demonstrated by Yoo et al (40) in NDV-infected cells, supports a role for SGs in the antiviral innate immune response (40,41,47).…”
Section: Discussionsupporting
confidence: 87%
“…We barely observed TRIM25/MAVS colocalizations. TRIM25 was previously shown to localize with stress granules (SGs) during Newcastle disease virus (NDV) infection (40). To further characterize the localization of TRIM25 after SeV infection, we performed immunofluorescence assays in mock-and SeVinfected cells with the SG markers TIAR and GB3P.…”
Section: Analysis Of Endogenous Rig-i Trim25 and Mavs Localization mentioning
confidence: 99%
“…A significant fraction of transfected cells in our system contain G3BP1-induced stress granules, and we previously showed that assembly of large G3BP1-induced SGs triggers PKR activation. Therefore, we considered whether G3BP1-induced SGs could recruit PKR, similar to findings reported for virus-induced SGs (12,33). When G3BP1 was expressed in HeLa cells, G3BP1 KO MEFs, and U2OS cells and stained for PKR, we found that PKR strongly colocalizes with G3BP1-induced stress granules in all cell types (Fig.…”
Section: G3bp1 and G3bp1-induced Sgs Restrict Enterovirus Infectionsupporting
confidence: 76%
“…Rather than being inert structures, recent reports suggest SGs have antiviral properties; the granules concentrate and promote interactions between a number of innate immune activators, their downstream interferon-stimulated genes (RIG-I, PKR, MDA5, and OAS), and their targets (5,41,43). For example, pattern recognition receptors like RIG-I are activated upon binding to viral RNAs in SGs, which leads to the stimulation of interferon-related genes (42,43,82). Alternatively, recent studies suggest that in the absence of virus infection, SGs can activate innate immune signaling (11,83,84).…”
Section: Discussionmentioning
confidence: 99%